BEATING BANKS THROUGH KNOWLEDGE - Monica CALU; Costel STANCIU (Challenges of the Knowledge Society)
In Romania, in the last decade, a significant number of solutions favorable to consumers with foreign currency denominated loans were obtained in courts against the banks or non-bank financial institutions. The judges noted the unfairness of the contractual terms inserted in the loans agreement and absolute nullity of these clauses. Also, in the context of the global economic and financial crisis triggered by the collapse of the banking system with the consequence of depreciation and/or sudden and high fluctuation of domestic currencies against the “safe-heaven currencies”, the theory of unpredictability becomes a particularly important institution. This paper deals with the concepts of „abusive clauses”, „unfair commercial practices” and „providing untruthful information to consumers to influence their choices”. It is also presenting a view of good faith and equity on the performance of contract and the “distribution of the risk” of the contract in the conditions of applying to the “unpredictability theory” in the context of terms of law doctrine and the relevant case law. The objective of this study is to demonstrate that by applying the theory of unpredictability to the occurrence of currency risk associated with loans in foreign currency and by subjecting to examination by court to the clauses whereby the consumer must assume the risk given by the changing of the circumstances of the execution of the contract can be obtain by the consumer or a rebalancing of the understanding of the parties or the cancellation clause which significantly unbalanced the consumer's obligation to bear any risk.